A comparative study between flipped classroom and traditional lecture-based classroom in first year medical students - Aggarwal, Kavita; Thakur, Bhaskar; Agrawal, Mahesh; Jhajharia, Sumit; Madaan, Himanshu; Mahapatra, Sri Krushna (International Journal of Research in Medical Sciences, 2019)
Introduction: Flipped classroom is a new pedagogical model in which students are provided with study resource material to develop a basic understanding of the topic before class, and in-class precious time is used for learner-centric activities. Accordingly the study objectives were to compare the effect of flipped and traditional classroom teaching method and to determine the student’s perception of flipped and traditional teaching method. Method: This was a non-randomized experimental study. A detailed multiple choice question based test was used to assess the knowledge gain. Another structured questionnaire on students’ perception on flipped classroom teaching and traditional teaching technique was used for both the groups. Results: A total of 112 students participated in this study. The mean assessment scores in the flipped and traditional classroom were not statistically significant. We observed in the current study that the qualitative response was better as compared to quantitative response. Conclusion: As per our qualitative observation, a hybrid of both traditional and flipped classroom teaching method can be used in the transition period until the acceptance for new innovative methods increase. Long term learning gain may be attained by improving motivation and engagement of students in learning process.